Comparative Study on different Video HidingTechniques - Saravanan, P; Thyagarajan, K. K (International Journal of Computer Sciences and Engineering, 2025)
In general, the data or information hiding mechanism with different perspective is a recent trend in the video data hiding and protection on-going research issues. For the most part of the video data hiding focuses on video content in different phases with modern cryptographic algorithms in order to secure from unauthorized access over the communication channel or network. In our previous research work contemplate its focuses on the data or textual content hiding mechanism over the content sharing among different clients through networks. The objective of the previous research is achieved with the help of data compression mechanism and hiding aspect in new direction regarding to protect the multimedia data content. This research paper describes the progress in the field of video steganography and intends to give the comparison between its different uses and techniques